The Dynastic Transmission of Power, Exit Options and the Coevolution of Rent-Seeking Elites - Arthur Silve; Thierry Verdier; Thierry Verdier (Center for Economic Studies and ifo Institute (CESifo), 2023)
We introduce a dynamic model that investigates the persistence and evolution of elite-dominated societies, where inherited political capital determines one's social standing. Our analysis highlights the critical role of the distribution of exit options in the evolution of political inclusiveness across generations. An elite comparatively more mobile than the masses generally entrenches a politically stratified society, whereas a more widespread distribution of exit options can encourage inclusiveness. Under certain conditions differential mobility may still induce political inclusiveness across generations. Exit options across different political entities lead to a joint evolution of local power structures.
Keywords: D72; F42; H26; P16; P48; 330; political dynasties; elite dynamics; exit options; rent-seeking; political spillovers